FILSAFAT ETIKA MASYARAKAT ISLAM JAWA: KONSEP BAIK DAN BURUK - Daryono Daryono (UIN Raden Mas Said Surakarta, 2021)
This article are based on library research regarding the concept of good and bad in the perspective of Javanese Muslim thought. The aim is to revise the designation of santri, priyayi and abangan and on the other hand to understand the Javanese ethics which are thought to be relativism ethics but on one side for respect attitudes and harmony with its moral values can create prosperity and progress even in post-colonial conditions. These values and results are suitable for the world view and life of Javanese Muslims whose transcendental rational vision is symbolized by Bima reaching kawruh sangkan paraning dumadi and Semar who live always under the guidance of the Divine. The success of this vision may be similar to the time when King Mangkunegara IV achieved the progress, among other things, even though it was in post-colonial conditions but during the time it was called Kala Sumbaga, a prosperous period. Therefore it can be an alternative thought for the advancement of the present and future.